Pengaruh Infeksi Beberapa Jenis Virus terhadap Penurunan Hasil pada Tanaman Cabai Rawit (Capsicum frutescens L.) - I WAYAN SUKADA; I MADE SUDANA; I DEWA NYOMAN NYANA; GEDE SUASTIKA; KETUT SIADI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2014)
ABSTRACT Effect of Infection of Some Viruses to the Decresing Yield on Rawit Pepper (Capsicum frutescens L.) This study aims to identify the types of viruses that infect the plants of chili pepper ( Capsicum frutescens L. ) in Kerta village, and to know the influence of some kind of viruses infection on yield decline. To verify the type of virus is done by taking a sample of the pepper plant leaf showing symptoms of the virus that has been demonstrated through serological and molecular tests. The results of this study indicate that the mosaic symptomatic chilli pepper plants were infected by some kind of virus such as CMV, TMV, and ChiVMV. Chilli pepper shows asymptomatic yellow were infected by the PepYLCV and chlorosis were infected by Polerovirus. The result of fruit chili harvest were showed the higher yields on the healthy plants with average 16.01 tonnes/ha, while the chilli that showed chlorosis symptomps were 8.42 tonnes/ha, and yellow symptomps were 3.07 tonnes/ha. The lowest were in the plants that shows mosaic symptomp with average 2.52 tonnes/ha. The virus infection caused the losses of yield of 47.40% in chlorosis symptomatic plants, 80.82% in the yellow symptomatic plant and 84.25%, in the mosaic symptomatic plants compared to healthy plants. High yield loss in the mosaic symptomatic plants were caused by the highest infection on chiilli pepper that infected by some kind of viruses.   Keywords : Chili pepper , mosaic, chlorosis, and yellow